HUBUNGAN BULLYING TERHADAP KEPERCAYAAN DIRI REMAJA KELAS VII DI MTS NEGERI 2 KEBUMEN - Wulan Rahmadhani; Eni Indrayani; Ois Novitarini (Jurnal Ilmu Kebidanan, 2023)
Background: The bullying becomes an infinite risk over time. In Indonesia, the number of cases of victims of bullying has always increased significantly, even the figure is reluctant to decrease. The results of conducted in five Asian countries by the (International Center for Research on Women (ICRW) (2015)), stated that Indonesia occupies the first level in the incidence of bullying in schools with a percentage of 83%.. As a result of this aggressive behavior of the bully prevents the child from expressing his feelings, because bullying doesn’t calm, makes the perpetrator feel stressed, which causes him to lack confidence, shame, difficulty focusing and anxiety, so that he cannot blend into the surrounding environment Objective: To know the relationship of bullying to the self-confidence of class VII teenagers in MTS Negeri 2 Kebumen Method: This study quantitative research with observational cross sectional design . The sample size in this study were 224 respondents using the total sampling technique. Bivariate analyze was carried out using the Chi-square test with a significant level of 95%, Result:. The results of the Chi-Square test obtained was used a p-value of 0.012 <0.05, and it can be concluded that there is a relationship between bullying and the self-confidence of class VII teenagers in MTS Negeri 2 Kebumen Conclusion: Bullying relationship to the self-confidence of class VII teenagers in MTS Negeri 2 Kebumen.